Secretory Autophagy and Its Relevance in Metabolic and Degenerative Disease - Gonzalez, Claudio Daniel; Resnik, Roxana; Vaccaro, Maria Ines (Frontiers in Endocrinology, 2020)
Proteins to be secreted through so-called “conventional mechanisms” are characterized by the presence of an N-terminal peptide that is a leader or signal peptide, needed for access to the endoplasmic reticulum and the Golgi apparatus for further secretion. However, some relevant cytosolic proteins lack of this signal peptides and should be secreted by different unconventional or “non-canonical” processes. One form of this unconventional secretion was named secretory autophagy (SA) because it is specifically associated with the autophagy pathway. It is defined by ATG proteins that regulate the biogenesis of the autophagosome, its representative organelle. The canonical macroautophagy involves the fusion of the autophagosomes with lysosomes for content degradation, whereas the SA pathway bypasses this degradative process to allow the secretion. ATG5, as well as other factors involved in autophagy such as BCN1, are also activated as part of the secretory pathway. SA has been recognized as a new mechanism that is becoming of increasing relevance to explain the unconventional secretion of a series of cytosolic proteins that have critical biological importance. Also, SA may play a role in the release of aggregation-prone protein since it has been related to the autophagosome biogenesis machinery. SA requires the autophagic pathway and both, secretory autophagy and canonical degradative autophagy are at the same time, integrated and highly regulated processes that interact in ultimate cross-talking molecular mechanisms. The potential implications of alterations in SA, its cargos, pathways, and regulation in human diseases such as metabolic/aging pathological processes are predictable. Further research of SA as potential target of therapeutic intervention is deserved.